The effect of paclitaxel- and fisetin-loaded PBM nanoparticles on apoptosis and reversal of drug resistance gene ABCG2 in ovarian cancer - Melayshia McFadden; Santosh Kumar Singh; Briana Kinnel; Sooryanarayana Varambally; Rajesh Singh (BMC, 2023)
Abstract Background High-grade serous ovarian cancer (OvCa) is the most common type of epithelial OvCa. It is usually diagnosed in advanced stages, leaving a woman's chance of survival below 50%. Despite traditional chemotherapeutic therapies, there is often a high recurrence rate following initial treatments. Hence, a targeted drug delivery system is needed to attack the cancer cells and induce apoptosis, overcome acquired drug resistance, and protect normal cells from cytotoxicity. The present study shows that targeting folate receptor alpha (FRα) through planetary ball milling (PBM) nanoparticles (NPs) induces apoptosis in OvCa cells. Results Human tissue microarrays (TMAs) show overexpression of FRα in Stage IV OvCa tissues compared to matched normal tissues. They provide a focus for a targeted delivery system. We formulated PBM nanoparticles encapsulated with paclitaxel (PTX) or fisetin (Fis) and conjugated with folic acid (FA). The cytotoxic effect of these PBM NPs reduced the concentration of the toxic chemotherapy drug PTX by five-fold. The combined treatment of PTX-FA NPs and Fis-FA NPs inhibited cell proliferation and induced apoptosis more extensively than the individual drugs alone. Apoptosis of OvCa cells, determined by flow cytometry, showed an increase from 14.4 to 80.4% (OVCAR3 cells) and from 2.69 to 90.0% (CAOV3 cells) in the number of apoptotic cells. Also, expressions of the pro-apoptotic markers, BAK and active caspase-3, were increased after PTX-FA + Fis-FA PBM NP treatment. In addition to looking at targeted treatment effects on apoptosis, drug resistance was investigated. Drug resistance in OvCa cells was reversed by ABCG2, an ABC-transporter marker. Conclusions Our study shows that PTX-FA and Fis-FA PBM NPs directly target platinum-resistant OvCa cells, induce cytotoxic/apoptotic effects, and reverse multi-drug resistance (MDR). These findings allow us to create new clinical applications using PTX-FA and Fis-FA combination nanoparticles to treat drug-resistant cancers.